EFFECTIVE WAYS TO INCREASE VOCABULARY IN LEARNING LANGUAGE - Fayzullaeva, Madina (Журнал иностранных языков и лингвистики, 2021)
To teach students how to memorize words, to inform them about the methods available, to teach them to use the most convenient methods of increasing vocabulary, and to put them into practice. The article is about increasing vocabulary and closely assisting in the acquisition of new knowledge.